Pressure-induced superconductivity extending across the topological phase transition in thallium-based topological materials - Pei, Cuiying; Huang, Peihao; Zhu, Peng; Liu, Linlin; Wang, Qi; Zhao, Yi; Gao, Lingling; Li, Changhua; Cao, Weizheng; Lv, Jian; Li, Xiang; Wang, Zhiwei; et al. (Cell Reports Physical Science, 2022)
The coexistence of superconductivity and topology holds the potential to realize exotic quantum states of matter. Here, we report superconductivity induced by high pressure in three thallium-based materials, covering the phase transition from a normal insulator (TlBiS2) to a topological insulator (TlBiSe2) through a Dirac semimetal (TlBiSeS). By increasing the pressure up to 60 GPa, we observe superconductivity phase diagrams with maximal critical temperature (Tc) values at 6.0–8.1 K. Our density functional theory calculations reveal topological surface states in superconductivity phases for all three compounds. Our study paves the path to explore topological superconductivity and topological phase transitions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: high pressure; superconductivity; thallium-based materials; topological materials